Implications of Career Choice of Undergraduates on their Employability Prospects in the Fourth Industrial Revolution (4IR) - Fasanmi, Success Ayodeji (Research in Social Sciences and Technology, 2023)
Choice of career is one of the most important decisions that everyone makes in life. This choice in most cases determines placement in the workplace. The determinants of the choices students make career-wise include parents, peers, passion and perceived prospects among others. The choice of career made by individuals have long-term implications on their employability status most especially in the Fourth Industrial Revolution (4IR) which aims at raising global income levels and improve the quality of life for populations around the world through applied science and technology. The descriptive survey research design was adopted for the study. The multi-stage sampling procedure was used. A purposive sampling technique was used to select five faculties out of the existing thirteen faculties at Obafemi Awolowo University, Ile-Ife, Nigeria. Five hundred (500) undergraduates were selected across the five selected faculties using simple random sampling technique with 100 students selected from each faculty. Descriptive and Inferential statistics were used to analyse the data collected for the study. The study found out that parental values and expectations has significant influence on the career choice of students and that career choice in turn has significant relationship with their employability prospects. The paper recommended among others the need for students to be allowed to make their career choices based on interest and ability with proper guidance by parents and surrogate parents.